Phenotypic and genotypic profiling of antimicrobial resistance in enteric Escherichia coli communities isolated from finisher pigs in Australia. Issue 10 (27th September 2016) - Smith, MG; Jordan, D; Gibson, JS; Cobbold, RN; Chapman, TA; Abraham, S; Trott, DJ
Abstract : Objective: To assess herd‐to‐herd variation in antimicrobial resistance phenotypes and associated antimicrobial resistance genes (ARGs) in faecal commensal Escherichia coli communities isolated from Australian slaughter‐age pigs. Methods: Hydrophobic grid‐membrane filtration (HGMF) was used to screen populations of E. coli isolated from faecal samples obtained from pigs prior to or at slaughter. Multiplex PCRs were applied to the pooled DNA extracted from the samples to identify specific ARGs. Methods: Pooled faecal samples from 30 finishers, from 72 different Australian pig farms, produced 5003 isolates for screening. HGMF techniques and image analysis were used to confirm E. coli resistance phenotypes to four antimicrobial agents (ampicillin, gentamicin, florfenicol and ceftiofur) using selective agars. Multiplex PCRs were performed on DNA from pooled samples for 35 ARGs associated with seven chemical classes. Results: The prevalence of E. coli isolates showing no resistance to any of the drugs was 50.2% (95% confidence interval (CI) 41.8–58.6%). Ceftiofur resistance was very low (1.8%; CI 0.8–3.9%) and no ARGs associated with 3rd‐generation cephalosporin resistance were detected. By contrast, ampicillin (29.4%, CI 22.8–37.0%), florfenicol (24.3%, CI 17.8–32.3%) and gentamicin (CI 17.5%, 10.7–27.2%) resistance prevalence varied greatly between farms and associated ARGs were common. The most common combined resistance phenotype was ampicillin–florfenicol. Conclusion: The use of registered antimicrobials in Australian pigs leads to the enteric commensal populations acquiring associated ARGs. However, despite a high intensity of sampling, ARGs imparting resistance to the critically important 3rd‐generation cephalosporins were not detected.